Framework for Environmental Protection in Nigeria - Thomas Eneji Ogar (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2021)
The evolution of Nigeria's environmental legal system is examined in this article. Like many other developing countries, Nigeria has had difficulty finding a balance between the expansion of its economy and the protection of its natural resources. Serious environmental problems, including the contaminating of groundwater in Lagos, the largest megacity in the nation, and the degradation of the marine environment in the Niger Delta by crude oil, reflect this dualism. The country's preoccupation with economic growth may be seen in the slow establishment of legal safeguards for natural resources, which has led to a despicable disrespect for the environment. This article claims that little progress has been achieved despite a growing knowledge of the need to safeguard natural resources. The significant and continued pollution of essential natural resources highlights this little progress. According to the inquiry, the administration that built these facilities is also one of the main offenders of environmental standards and laws. This often causes a system failure atmosphere in which nothing works and the environment suffers. Enforcing environmental standards has benefits such as increased employment opportunities, environmental protection, and environmental sustainability. Outdated laws, expensive environmental standards, weak institutional capacity, poor governance, understaffing, inadequate funding, vested interests, overlapping or conflicting legislation, ignorance, and a lack of the rule of law are a few of the challenges to effective compliance with environmental regulations.